Revealing bioremediation potential of novel indigenous bacteria from oil-contaminated sites in the UAE: A combined bioinformatics and experimental validation - Sara Awni Alkhatib; Sagar Arya; Deema Islayem; Runyararo Memory Nyadzayo; Sharmarke Mohamed; Ahmed F. Yousef; Hector H. Hernandez; Anna-Maria Pappa (PLoS ONE, 2025)
Microbial biodegradation of recalcitrant aromatic hydrocarbon pollutants represents an environmentally sustainable strategy for remediating contaminated sites. However, elucidating the metabolic capabilities and genetic determinants of biodegrading strains is crucial for optimizing bioremediation strategies. In this study, we comprehensively characterize the aromatic catabolic potential of two indigenous bacterial isolates, A. xylosoxidans C2 (A. x. C2) and A. xylosoxidans KW38 (A. x. KW38), obtained from hydrocarbon-impacted environments in the United Arab Emirates (UAE). Experimental validation through aromatic hydrocarbons supplemented growth studies confirmed the capability of the isolated bacteria to mineralize bisphenol A, 4-hydroxybenzoic acid, 1-naphthalenemethanol, and the high molecular weight polycyclic aromatic hydrocarbon (PAH), pyrene, in the presence of glucose. Their degradation efficiencies were comparable to or greater than those of Pseudomonas paraeruginosa, a well-characterized model organism for aromatic compound degradation. Integrated bioinformatic analyses uncovered fundamental aromatic catabolic pathways conserved across Achromobacter species, along with strain-specific genes that potentially confer specialized degradative capacities, highlighting the genomic basis of the observed metabolic versatility. Further, protein modeling based on the curated sequences revealed unique features of individual catabolic enzymes and their interaction networks. Notably, a dehydrogenase enzyme involved in aromatic ring cleavage was identified exclusively in these UAE isolates. These findings establish A. x. C2 and A. x. KW38 as promising bioremediators of diverse aromatic pollutants. Overall, the study exemplifies a powerful and comprehensive methodological framework that bridges bioinformatic analysis and experimental research to further optimize the effectiveness of experimental design. We achieved a substantial reduction in the number of unknown genetic and metabolic determinants of aromatic hydrocarbon degradation in the strains, reducing uncertainty by 99.3%, thereby enhancing the overall process and outcomes for systematic biodiscovery of pollutant-degrading environmental microbes to address ecological challenges.